Migration inhibitory factor and cluster of differentiation 74‐mediated dendritic cell apoptosis exacerbates acute acetaminophen‐induced liver injury - Zezhou Wu; He Luan; Jinghui Huang; Boming Liao; Fang Xiao (Immunity, Inflammation and Disease, 2023)
Abstract Introduction We investigated the role of macrophage migration inhibitory factor (MIF) on dendritic cells (DC) during acetaminophen (APAP)‐induced acute liver injury (ALI) in mice. Methods First, we randomly divided the mice into experimental (ALI model) and control groups, then intraperitoneally injected 600 mg/kg of APAP or phosphate‐buffered saline, respectively. Then, we collected liver tissue and serum samples to evaluate liver inflammation using serum alanine aminotransferase level and hematoxylin and eosin (H&E) staining of liver tissues. Flow cytometry was used to identify changes in the quantity and percentage of DCs, as well as the expression of cluster of differentiation (CD) 74 and other apoptosis‐related markers in the liver. Next, we randomly divided the mice into APAP‐vehicles, APAP‐bone marrow‐derived dendritic cells (BMDCs), APAP‐MIF, APAP‐IgG (isotype immunoglobin G antibody) groups (four mice per group), after APAP injection, we injected control extracts, BMDCs, mouse recombinant MIF antibodies, or IgG antibodies into the tail vein. Lastly, the severity of the liver injury and the number of DCs were assessed. Results The APAP‐induced ALI mice had increased hepatic MIF expression but significantly lower amounts of hepatic DCs and apoptotic DCs than healthy mice; CD74 expression on the HDCs also increased markedly. Supplementing APAP‐induced ALI mice with BMDCs or MIF antibodies significantly increased the number of hepatic DCs compared with the control mice, alleviating liver damage. Conclusion The MIF/CD74 signaling pathway may mediate hepatic DC apoptosis and promote liver damage.